Evaluation of the Level of Dynamic Thiol/Disulphide Homeostasis in Adolescent Patients with Newly Diagnosed Primary Hypertension - Cakici, Evrim Kargin; Eroglu, Fehime Kara; Yazilitas, Fatma; Bulbul, Mehmet; Gur, Gokce; Aydog, Ozlem; Elhan, Atilla Halil (Springer, 2018)
Background Thiol/disulphide homeostasis plays a critical role in numerous intracellular enzymatic pathways including antioxidant defense and detoxification. This study was designed to investigate the impact of thiol/disulfide homeostasis in adolescent patients with recently diagnosed primary hypertension (HT) using a novel and automated method. Methods Native thiol/disulphide levels were measured by a novel spectrophotometric method (Cobasc 501, Roche Diagnostics, Mannheim, Germany) in 30 patients with primary HT together with 30 healthy controls. Results The levels of native thiol, total thiol, and native thiol/total thiol ratios were significantly lower, while the disulphide level, disulphide/native thiol, and disulphide/total thiol ratios were significantly higher in patients with primary HTcompared with the control group. There were significant positive correlations between 24-h mean systolic and diastolic blood pressure and disulphide levels, disulphide/native thiol, and disulphide/total thiol ratios. A multiple linear regression model showed that a disulphide/native thiol ratio above 5 and family history of HT are independent predictors of HT. Conclusions Our study showed that dynamic thiol/disulphide homeostasis shifted towards disulphide formation in adolescent patients with primary HT. Understanding the role of thiol/disulfide homeostasis in primary HT might provide new therapeutic intervention strategies for patients.
Keywords: Oxidative Stress; Dynamic Thiol/Disulphide; Oxidized Thiol; Blood Pressure; Adolescents